Contribution of diet and major depression to incidence of acute myocardial infarction (AMI). - Yary, Teymoor; Soleimannejad, Kourosh; Abd Rahim, Firdaus; Kandiah, Mirnalini; Aazami, Sanaz; Poor, Seyedehozma Jafar; Wong, Teck Wee; Aazami, Golnaz (BioMed Central, 2010)
Background. Despite significant improvements in the treatment of coronary heart disease (CHD), it is still a major cause of mortality and morbidity among the Iranian population. Epidemiological studies have documented that risk factors including smoking and the biochemical profile are responsible for the development of acute myocardial infarction (AMI). Psychological factors have been discussed as potential risk factors for coronary heart disease. Among emotional factors, depression correlates with coronary heart disease, particularly myocardial infarction.